Voluntary Agreements in Environmental Protection - Experiences in Germany and Future Perspectives - Klaus Rennings; Karl Ludwig Brockmann; Heidi Bergmann (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1997)
A trend towards softer regulation, especially in the form of negotiated environmental agreements, is observable in national and international environmental policies. Such agreements are controversial, because there are fears that government will relinquish its responsibility for environmental protection. This paper analyses recent experiences with voluntary agreements in Germany. Topical German examples that have prompted public debates include the takeback agreement for cars, the voluntary agreement made by a number of industries on a C02 reduction by the year 2005 and the voluntary agreement made by the automobile industry on the development of energy-efficient cars. Proponents of voluntary agreements argue that this instrument provides incentives to the business sector for the development of efficient, innovative and environmentally-friendly solutions. Analysing the examples mentioned above, we conclude that it is hard to detect solutions derserving such attributes. These agreements are unlikely to produce results that go beyond what industry would have done in any case and they avoid using economic incentives. The agreements are' non-binding and unenforceable, with the negotiating process leading to a watering down of the environmental goals government had originally aimed at. A preference for negotiated solutions on principle, as currently espoused by the Federal Government in Germany, seems to be counterproductive. If the government clearly signals its willingness to refrain from using regulatory or economic instruments in favour of industry agreements, it weakens its negotiating position. The government also limits its options should the implementation of the agreement prove unsatisfactory. Government needs to be 'in control in order to leave its choice of policy instruments open and to be flexible. In a last step, we derive some general conclusions concerning reasonable strategies and applications of voluntary agreements within the European Union.
Keywords: 330; negotiated agreements; climate protection; circular economy; economic instruments of environmental policy